2009
DOI: 10.1111/j.1365-2133.2009.09094.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear spectral imaging of human hypertrophic scar based on two-photon excited fluorescence and second-harmonic generation

Abstract: All the measurements were performed in backscattering geometry and demonstrated that nonlinear spectral imaging has the ability to differentiate hypertrophic scar tissue from normal skin based on noninvasive SHG imaging, and TPEF imaging revealed the microstructure and spectral features of collagen and elastin fibres. With the advances in spectral imaging apparatus miniaturization, we have good reason to believe that this approach can become a valuable tool for the in vivo pathophysiology study of human skin h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 30 publications
5
53
1
Order By: Relevance
“…Several studies have shown that the collagen fibers are irregularly disordered without well-defined orientation in pathological samples, while the morphology of the collagen fibers is highly arranged in normal samples [12,[38][39][40][41][42]. This means that a detailed knowledge of the collagen morphology is very important because structural modifications of the fibrillar matrix are associated with various physiologic processes including cancer [9].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the collagen fibers are irregularly disordered without well-defined orientation in pathological samples, while the morphology of the collagen fibers is highly arranged in normal samples [12,[38][39][40][41][42]. This means that a detailed knowledge of the collagen morphology is very important because structural modifications of the fibrillar matrix are associated with various physiologic processes including cancer [9].…”
Section: Discussionmentioning
confidence: 99%
“…Elastin is functionally and spatially disorganized in scar tissue [28,29]. Expression of both elastin and fibrillin-1 are reduced in scar tissue with a particularly prominent reduction in hypertrophic scars [15].…”
Section: Discussionmentioning
confidence: 99%
“…Newly synthesized, elastic fibers in scar tissue always appear thin, fragmented, and less mature than elastic fibers in normal skin [15,29,30]. Even in scars older than 10 years, elastic fibers never reach the size and maturity of healthy skin [30], which attributes to the fact that hypertrophic scars are usually hard and inelastic [29].…”
Section: Discussionmentioning
confidence: 99%
“…Comparing biopsies taken from hypertrophic and keloid scars, Meshkinpour et al 153 also reported morphological differences in the local collagen microstructures reveled by SHG images. Chen et al 154 also reported imaging of human hypertrophic scars using TPEF and SHG. Later Da Costa et al 155 used SHG imaging to compare live human keloids and normal facial tissue and observed a swirling collagen morphology in keloids, compared with the typical wavy collagen structure in normal skin.…”
Section: Nonlinear Optical Imagingmentioning
confidence: 99%